Natural carbon stable isotope ratios as indicators of the relative contribution of live and inert diets to growth in larval Senegalese sole (Solea senegalensis) - Gamboa Delgado, Julián; Cañavate, José Pedro; Zerolo, Ricardo; Le Vay, Lewis (2008)
The relative contributions of live Artemia metanauplii and an inert diet for growth of Senegalese sole larvae and postlarvae were assessed through the analysis of carbon stable isotopes ratios (δ13C) in both diets and whole larval tissue. Larvae were reared on four dietary regimes: 100% live prey (rotifers and Artemia), 100% inert formulated diet and two co-feeding regimes of 70:30 and 30:70 ratios of Artemia and inert diet, respectively. Larvae from the live food regime and both co-feeding regimes showed a steep increase in δ13C from 10 days after hatching (DAH) as a result of the onset and continuation of Artemia consumption. From 12 DAH fish larvae from all the regimes showed significant isotopic differences as their δ13C increased to final asymptotic values of −15.1, −15.6 and −16.3‰ in the live food, 70:30 and 30:70 regimes, respectively. Carbon turnover rates in larvae from both live food and co-feeding regimes were relatively high (0.071 to 0.116 d−1) but more than 90% of the observed change in fish tissue isotopic values was accounted for by the retention of carbon in new tissue growth. A two-source, one-isotope mixing model was applied to estimate the nutritional contribution of Artemia and inert diet to postlarvae growth in the co-feeding regimes. At 23 DAH, the relative contribution of live and inert diets to tissue growth in larvae was respectively, 88 and 12% for the 70:30 co-feeding regime and 73 and 27% for the 30:70 co-feeding regime. At 17 DAH, the estimated proportion of tissue carbon derived from the inert diet was higher at 23 and 38% for the 70:30 and 30:70 regimes, respectively. The results suggest that co-feeding regimes in Solea senegalensis larvae may be adjusted to meet ontogenetic changes in the capacity for larvae to utilise inert diets. The contrasting levels of carbon isotope discrimination between diet and tissue in larvae reared on either 100% live feed or 100% inert diet indicate relatively poor utilization of nutrients from the inert diet. The use of isotopic discrimination factors as potential indicators of the digestive physiological performance of a consuming organism in regards to its diet is discussed.